Geogenic and anthropogenic contamination in river water and groundwater of the lower Cauvery Basin, India - Keerthan, Lingaiah; RamyaPriya, Ramesh; Elango, Lakshmanan (Frontiers in Environmental Science, 2023)
Degradation of water quality is a major challenge in both developed as well as in developing countries since it poses a greater risk to ecological health. Cauvery river is one of the important rivers of southern India, where the effect of seasonal variation in the quality of river water and its adjoining groundwater on the lower part of the basin has not yet been studied. Hence, the present study was carried out to evaluate the river water and adjacent groundwater for drinking and irrigational purposes and also to identify the sources affecting the water quality. About 118 river water and 131 groundwater samples were collected once in four months from May 2018 to August 2019. The water samples were analyzed for EC, pH, major and minor ions and trace elements. The major, minor and trace elements were then compared with the Bureau of Indian Standards and World health organization for drinking water quality assessment. The drinking water quality was assessed, indicating that both river water and groundwater were unsuitable in the coastal regions, especially during dry seasons. Irrigation water quality was also assessed, which indicates that most of the river water and groundwater samples were unsuitable near the coastal region. The quality of river water and groundwater in the lower Cauvery basin was found to be good during wet periods compared to the dry season. It was observed that the rock water interaction was the major factor controlling the water quality for groundwater and surface water, followed by anthropogenic activities such as domestic sewage and effluents and runoff from irrigated lands. The study emphasized the development of a finer observational network for water quality, along with stringent monitoring of the disposal of contaminants in the rivers and groundwater.